PROFIL KETERAMPILAN ABAD KE-21 (21ST CENTURY SKILLS) MAHASISWA PADA PERKULIAHAN TEKNIK DAN MANAJEMEN LABORATORIUM PROGRAM STUDI PENDIDIKAN BIOLOGI FKIP UNIVERSITAS RIAU TAHUN AKADEMIS 2014/2015 - Asmawi, Wiwik; Fauziah, Yuslim; ', Arnentis (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract : This study aims to determine the profile of the 21st century skills student of Techniques and Laboratory management. This research is a descriptive, with a total population was all the students who took the course techniques and Laboratory management academic year 2014/2015. The research sample was determined by total sampling technique based on qualitative and quantitative data, sources of data derived from primary data. Primary data obtained from questionnaires collected, with 88 respondents. The parameters used are the 5 elements of the 21st century skills associated with techniques and laboratory management, including digital area literacy, inventive thinking, effective communication, high productivity and spirituality. Data collection instruments used in this study a questionnaire enclosed and open questionnaire. Data analysis technique used is descriptive technique. The result of data analysis showed that the profile of the 21st century skills students taking techniques and laboratory management gained an average of 3.91 (Good). Based on the results of this study concluded that students who take the course techniques and laboratory management academic year 2014/2015 has the potential to face the challenges of the 21st century.Keywords : 21st Century Skills, Techniques and Laboratory Management, Profile